سحب القرارات الادارية في التشريع الجزائري - سالمي اكرم - حاج حفصي مصطفى (المسيلة, 2023)
The administration exercises its administrative activity by means of the administrative decision, but it may issue illegal decisions that it must correct and restore the situation to what it was by means of the mechanism of withdrawing the administrative decision that terminates the administration retroactively with regard to the future and the past from the day of its issuance and considering it as if it was not. The administration withdraws the decision within the legally prescribed period, and according to certain procedures, where the withdrawal decision may be issued either automatically by the authority issuing the decision and at the request of the stakeholder. A number of conditions must be met in order for the withdrawal decision to be issued sound and productive with its effects, with the necessity of the administration’s commitment to restore the conditions to what they were.
Keywords: سحب القرارات الادارية - التشريع الجزائري